Investigating the Application of Singing Method in Learning State Primary School - Riskania, Ayu (Program Magister Teknologi Pendidikan Universitas Jambi, 2021)
This research investigates the application of the singing method in learning in class II of SD Negeri 35/I Tebing Tinggi with a focus on the teacher's efforts in creating a pleasant learning atmosphere and increasing student involvement. Qualitative research methods are carried out through observation, interviews and data analysis of learning using the singing method. The research results show that lesson planning is key in implementing this method, with teachers choosing songs that suit the characteristics of students and learning material, as well as changing song lyrics to suit the content of the material. In addition, the introduction of songs and the addition of simple movements become an integral part of the learning process. It was found that students showed a positive response to the singing method, became more active, enthusiastic, and did not feel pressured in learning. The novelty of this research lies in a creative approach to learning that attracts students' attention, increases their participation, and encourages better understanding of the material. The practical implication is that teachers need to pay attention to careful learning planning to implement the singing method effectively, thereby creating a positive learning environment and strengthening student learning outcomes.